Measuring socioeconomic position in studies of health inequalities - Lindberg, Marie Hella (UiT The Arctic University of Norway, 2024)
There is a consistent finding that the higher the socioeconomic position (SEP), the better the health. The choice of SEP indicator is crucial in explaining these socioeconomic inequalities. However, a poorly motivated use of SEP indicators prevails in the literature on social health inequalities, hampering the transparency and comparability across studies. Its primary aim is to explore different ways of measuring SEP to identify social inequalities in health. The thesis focuses on the most common, objective SEP indicators (education, occupation, and income); subjective SEP; and childhood circumstances. This thesis consists of three papers. Papers I and III apply data from the Tromsø Study, and Paper II is based on an online survey investigating people's views on SEP, conducted in Norway and Australia. Paper I investigates the potential to combine education and income into a composite score for SEP and how it predicts inequalities in health-related quality of life (HRQoL). Paper II assesses the relative importance of objective SEP indicators and childhood circumstances in estimating subjective SEP. Paper III explores the role of circumstances and lifestyle factors in estimating inequalities in HRQoL and self-rated health. While we found that the combination of education and income demonstrated a non-linear relationship with overall SEP, the composite SEP score was not superior as a predictor of HRQoL compared to including education and income separately. Furthermore, we found that childhood circumstances demonstrated a lasting, independent impact on subjective SEP. Paper III revealed that there were inequalities arising from circumstances, with substantial contributions from financial circumstances in childhood and education. This thesis demonstrates the need to motivate the choice of SEP indicator in studies of health inequalities. It also stresses the importance of early-life factors as determinants of adult health, advocating for policies targeting childhood circumstances in equalising early life chances. Et ...